A educação ambiental e os resíduos de serviços de saúde na formação dos acadêmicos de odontologia e enfermagem em Francisco Beltrão – PR - Graniska, Angela Ariane Dalzoto (2018)
The management of health care waste (SSR) or solid residues of health services (SSR) has been a major challenge in the national territory in terms of its potential for public, occupational and environmental health. Part of the problem lies in the process of proper segregation and disposal of RSS, which directly involves the internal and external dimensions of the generating institutions of this specific class of waste. This research emerged from the questioning about the need for higher education institutions to improve the environmental education process, particularly regarding the RSS theme in the training of future professionals. The general objective of the study was to approach the knowledge related to the RSS theme in the process of training the students of the Dentistry and Nursing courses of the Institutions of Higher Education of the Municipality of Francisco Beltrão - PR. To this end, it was specifically carried out: survey and bibliographical analysis of the legislation pertinent to RSS; diagnosis and analysis of the knowledge that the academics of the superior courses of Dentistry and Nursing have on the RSS; elaboration of informative materials on segregation, packaging and identification of the RSS for the training of the students of the Dentistry and Nursing courses. In order to reach the objectives, a questionnaire with open and closed questions was applied to 78 (seventy eight) students of the undergraduate course in Dentistry of two Higher Education Institutions and 33 (thirty three) students of the undergraduate Nursing course. At the end of the research, it was possible to conclude that despite the current nature of RSS Environmental Legislation and the knowledge demonstrated by the students of the Dentistry and Nursing courses regarding the types of RSS, it is possible to affirm that the definitions and classifications are not totally clear for the students, as they presented doubts about the proper segregation and disposal of the waste; to the professional responsible for the management of the waste generated; as well as the need for treatment prior to final disposal. In view of the research, it was observed the importance of developing a teaching methodology in order to overcome the lack of information, guide and standardize the operations involving RSS and the management carried out by health professionals in the context of the assistance provided to the population.